Surgical Technique Left gastric vein to adrenal vein anastomosis: intraoperative solution for gastric venous congestion following extended distal pancreatectomy - Fernández-Placencia, RM (2024)
Extended distal pancreatectomy often requires resection of vascular structures and adjacent organs, potentially leading to gastric venous congestion. This case report describes a 49-year-old female who underwent radical antegrade modular pancreatosplenectomy for pancreatic ductal adenocarcinoma. During the procedure, segmental gastric venous congestion was observed and resolved by anastomosing the left gastric vein to the left adrenal vein. The in-hospital postoperative recovery was initially uneventful; however, the patient was readmitted because of intra-abdominal fluid collection that was managed with antibiotics. Pathological examination confirmed moderately differentiated ductal adenocarcinoma with lymphovascular invasion. The patient received adjuvant mFOLFIRINOX therapy and remains disease-free 12 months after surgery with adequate patency of the anastomosis. This case highlights the importance of recognizing and addressing gastric venous congestion during radical antegrade modular pancreatosplenectomy to prevent complications, such as delayed gastric emptying or gastric necrosis, and proposes left gastric vein to left adrenal vein anastomosis as an effective intraoperative solution.